"Keaping" a lid on lung cancer: the Keap1-Nrf2 pathway. Issue 14 (18th July 2018) - Best, Sarah A.; Sutherland, Kate D.
ABSTRACT: Lung cancer remains one of the world's deadliest cancers, with effective targeted treatment options available for only a small subset of patients. The rapid expansion of cancer genomics in recent years has provided insight into the genetic landscape of all major lung cancer subtypes and led to new discoveries on the heterogeneous biology underlying lung tumorigenesis. Interestingly, these studies have revealed a high frequency of alterations in the Kelch-like ECG-associated protein 1 (KEAP1)–Nuclear factor erythoid–2–related factor 2 (NRF2) stress response pathway, for which no targeted treatments are currently available. In this review, we describe the molecular mechanisms underlying NRF2 pathway activation in lung cancer cells, with a focus on in vivo functional studies in genetically engineered mouse models. Importantly, potential avenues and implications for therapeutic targeting of KEAP1-NRF2 pathway vulnerabilities for lung cancer patients will be highlighted.